Two families of approximations for the gamma function - Feng, Lei; Wang, Weiping (Numerical algorithms, 2013)
In this paper, we establish two families of approximations for the gamma function: where the constants and can be determined by recurrences, and , , are parameters. Numerical comparison shows that our results are more accurate than Stieltjes, Luschny and Nemes’ formulae, which, to our knowledge, are better than other approximations in the literature.